2010
DOI: 10.1039/b924420d
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated compounds in maternal serum and cord blood from selected areas of South Africa: results of a pilot study

Abstract: There is limited information about both environmental and human perfluorinated compounds (PFCs) concentrations in the southern hemisphere, and for the first time, concentrations of these compounds are reported in maternal serum and cord blood of South African women. The majority of the participants were of African Black ethnicity, with a similar socioeconomic status. In maternal serum perfluorooctane sulfonate (PFOS) was found to be the most abundant PFC (1.6 ng mL ) and perfluorohexane sulfonate (PFHxS: 0.5 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
76
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 45 publications
12
76
6
Order By: Relevance
“…In the present study, we found higher levels of PFCs in maternal serum than in cord serum, which is consistent with previous studies (Monroy et al 2008;Hanssen et al 2010;Beesoon et al 2011). Maternal and cord PFOS and PFOA concentrations were among the highest in Europe (Midasch et al 2007;Fei et al 2007;Needham et al 2011) and even among the highest in the world (Liu et al 2011;Kim et al 2011a, b;Beesoon et al 2011).…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we found higher levels of PFCs in maternal serum than in cord serum, which is consistent with previous studies (Monroy et al 2008;Hanssen et al 2010;Beesoon et al 2011). Maternal and cord PFOS and PFOA concentrations were among the highest in Europe (Midasch et al 2007;Fei et al 2007;Needham et al 2011) and even among the highest in the world (Liu et al 2011;Kim et al 2011a, b;Beesoon et al 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Biomonitoring data showed 4-8 fold higher PFCs concentrations in blood plasma of population exposed to PFCs contaminated drinking water compared with controls (Holzer et al, 2008). These can also explain why the concentrations of PFOS and PFOA in this study were much lower than concentrations from developed countries like USA (Nelson et al, 2010), Japan (Harada et al, 2010) and Germany (Fromme et al, 2009), only higher than those reported for South Africa (Hanssen et al, 2010) and Peru (Calafat et al, 2006b).…”
contrasting
confidence: 39%
“…According to our hypothesis, the significantly lower %br-PFOS in American females could be a result of relatively lower PreFOS exposure compared to males. However, it might also be explained by isomer-selective placental transfer during pregnancy, which favors branched PFOS isomers and results in reduced %br-PFOS in maternal serum (Beesoon et al, 2011;Hanssen et al, 2010). Scarce isomer specific studies exist on menstrual and lactation elimination of PFOS, however, the significantly higher %br-PFOS in the husbands than their wives, none of which have had a baby (Zhang et al, 2014), may point to a preferential branched PFOS elimination in females.…”
Section: Temporal Trends Of %Br-pfosmentioning
confidence: 75%
“…In rats, there was no evidence for enantioselective urinary elimination or tissue distribution (Wang et al, 2011b), but species differences could exist. The observed age and sex differences could possibly explained by enantioselective elimination through menstrual bleeding (Knox et al, 2011), placental transfer (Beesoon et al, 2011;Hanssen et al, 2010) and lactation Karrman et al, 2007) in young women, but enantioselective studies of these processes have not been done for PFOS, thus it is acknowledged that there remains some uncertainty in interpreting 1m-PFOS EF data.…”
Section: Temporal Trends Of 1m-pfos Efmentioning
confidence: 94%